The family Pleosporaceae: Intergeneric relationships and phylogenetic perspectives based on sequence analyses of partial 28S rDNA - Kodsueb R. (2014)
The Pleosporaceae is an important loculoascomycete family. There has been disagreement, however, regarding the taxonomic placement of many genera within this family. This study investigates phylogenetic relationships among the genera Cochliobolus, Kirschsteiniothelia, Leptosphaerulina, Macroventuria, Pleospora, Pyrenophora, and Wettsteinina. Partial 28S rDNA sequences from taxa within these genera were analyzed with maximum parsimony, likelihood and Bayesian methods. Cochliobolus can be segregated broadly into two groups as previously proposed. Pleospora is polyphyletic in its current sense. Taxa with Stemphylium anamorphs are closely related to Cochliobolus and fit within the Pleosporaceae, whereas the affinities of Pleospora herbarum and P. ambigua are still ambiguous. Pyrenophora constitutes a monophyletic group within the Pleosporaceae, whereas Leptosphaerulina and Macroventuria appear to share phylogenetic affinities with the Leptosphaeriaceae and Phaeosphaeriaceae. Phylogenies indicate that Wettsteinina should be excluded from the Pleosporaceae. Similar findings are reported for Kirschsteiniothelia, which is probably polyphyletic. Anamorphic characters appear to be significant (especially in Cochliobolus) while ascospore morphologies, such as shape and color and substrate occurrence are poor indicators of phylogenetic relationships among these loculoascomycetes. © 2006 by The Mycological Society of America.